Location area planning problem in WiMAX networks using nature inspired techniques: performance study. (2017) - Sangeetha, J.; Goel, Nikhil; Rustagi, Ram P.; Murthy, K.N. Balasubramanya
Worldwide Interoperability for Microwave Access (WiMAX) is a broadband wireless technology that provides an efficient service to mobile stations (MS). Whenever there is a need to establish communication and provide service to MSs, the network has to track the location of the MSs through the base station. Tracking the location of the MSs is a very difficult and complex problem in the WiMAX network. This paper discusses a location area planning problem, which can be solved by partitioning the WiMAX network into location areas, so that the cost per call arrival is minimum. Finding the optimal number of location areas and the corresponding configuration of the partitioned network is an NP-complete problem. In this study, we use nature inspired techniques, namely, genetic algorithm (GA), artificial bee colony (ABC) and artificial immune system (AIS) to find an optimal solution to the location area planning problem. The performance is analysed and compared for all these nature inspired techniques. In this study, we also compare these techniques to gauge their suitability for solving the location area planning problem. From the obtained results, we conclude that ABC gives better optimal solution and AIS takes less computational time to locate the optimal solution.